The Utilization Ethnobotany Spice Based On Sundanese Local Wisdom Community in Kelurahan Gununggede Subdistrict Kawalu Tasikmalaya City As Teaching Materials Supplement - Sambung Nadiyawati; Diana Hernawati; Rinaldi Rizal Putra (Universitas Lampung, 2023)
The purpose of this study is to describe an ethnobotanical study of the use of spices based on local wisdom in the Sundanese people in Gununggede Village, Kawalu District, Tasikmalaya City. This research method was carried out in a qualitative descriptive manner with semi-structured observation and interview techniques. The selection of respondents using purposive snowball sampling method and obtained the number of respondents as many as 20. The results showed 31 types of plants belonging to 17 families. Zingiberaceae is the most common family with 6 species. The results of the analysis use the cultural significance index (ICS). The results showed that the highest ICS value was 30 for shallots (Allium cepa) and garlic (Allium sativum) and the lowest 9 for chili bendol (Capsicum chinense) and vegetable starfruit (Averrhoa bilimbi). The results of this study can be concluded that plant species with high ICS values are the species most frequently used and their function cannot be changed in cooking dishes.Â DOI: http://dx.doi.org/10.23960/jbt.v11.i1.27172